Menguji Keberadaan N-Shaped Environmental Kuznets Curve di Indonesia dengan Model ARDL - Sunaryo, Ridwan Pandu; Tajib, Erny (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
The study aims to test the existence of the N-shaped Environmental Kuznets Curve (EKC) and to determine the impact of fossil energy consumption and economic activity such as industrialization, urbanization, and trade openness on CO2 emissions in Indonesia from 1971 to 2021, using Autoregressive Distributed Lag (ARDL). The results of this study show that the relationship between per capita GDP and CO2 emissions in Indonesia has a reversed N-shape. Industrialization and per-capita consumption of fossil energy have a positive impact, while trade openness has a negative impact on CO2 per-capita emissions both in the short and long term. Meanwhile, urbanization negatively affects CO2 emissions per capita, but only in the long run.